ANALISIS REALISASI ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) PADA DINAS KOMUNIKASI DAN INFORMATIKA PROVINSI KALIMANTAN TIMUR TAHUN 2016-2020i - Ida Rahmawati3, Vebi Regina Imam Nazarudin Latif2 (EKONOMIA, 2021)
Analysis of the Realization of the Regional Revenue and Expenditure Budget (APBD) at the Communication and Informatics Office of East Kalimantan Province 2016-2020. The research objective to be achieved is to find out and analyze whether the average performance of Operational Expenditures against Total Regional Expenditures at the Communication and Informatics Office of East Kalimantan Province in 2016-2020 is very harmonious when viewed from the Analysis of Expenditure Harmony. To find out and analyze whether the average Performance of Capital Expenditures against Total Regional Expenditures at the Communication and Information Technology Office of East Kalimantan Province . The theoretical basis used is that financial management is one of the company's operational functions which is very important among the company's other operational functions. Original Regional Revenue (PAD) is all regional revenue that comes from original regional economic sources. The results of this study are the average performance of the ratio analysis of Operational Expenditures to Total Regional Expenditures at the Office of Communication and Information Technology of East Kalimantan Province in 2016-2020 is very harmonious, because Regional Expenditures and Operational Expenditures are realized by the budget well and Analysis of the Correspondence of Capital Expenditures against Total Regional Expenditures at the Office of Communication and Information Technology of East Kalimantan Province in 2016-2020 are not harmonious